2006
DOI: 10.1210/jc.2006-1719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Amino-Terminal-Specific Antiglutamate Decarboxylase (GAD65) Autoantibodies with β-Cell Functional Reserve and a Milder Clinical Phenotype in Patients with GAD65 Antibodies and Ketosis-Prone Diabetes Mellitus

Abstract: DPD-defined epitope specificity is correlated directly with preserved beta-cell functional reserve in GAD65Ab-positive patients and is associated with the milder clinical phenotype of A+B+ KPDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Thus, anti-GAD65 reactive with ctc1, as defined by blocking by rFab from mAbs b78, DPD, and DPC, was associated with enzyme inhibitory antibodies, whether from patients with Stiff Person Syndrome (22) or a subset of ketosis-prone type 1 diabetes with a higher ␤-cell functional reserve and a more benign clinical course (23). Also, anti-GAD65 reactive with ctc1/NH 2 -terminal epitopes was associated with slowly progressive type 1 diabetes, i.e., latent autoimmune diabetes of adults (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anti-GAD65 reactive with ctc1, as defined by blocking by rFab from mAbs b78, DPD, and DPC, was associated with enzyme inhibitory antibodies, whether from patients with Stiff Person Syndrome (22) or a subset of ketosis-prone type 1 diabetes with a higher ␤-cell functional reserve and a more benign clinical course (23). Also, anti-GAD65 reactive with ctc1/NH 2 -terminal epitopes was associated with slowly progressive type 1 diabetes, i.e., latent autoimmune diabetes of adults (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the rationale underlying this classification and nomenclature for KPD (3,8); briefly, they specify important differences in phenotype and natural history that are obscured in the current American Diabetes Association classification scheme, wherein both ␤Ϫ subgroups would be termed type 1 diabetes and both ␤ϩ groups would be termed type 2 diabetes. With the exception of the strong autoimmune basis for ␤-cell functional loss in Aϩ␤Ϫ KPD (11,12), the factors underlying irreversible or reversible severe ␤-cell dysfunction in the KPD subgroups remain unclear and may be complex, even for the other subgroup with an apparent autoimmune basis (Aϩ␤ϩ KPD) (13).…”
mentioning
confidence: 99%
“…By contrast, rFab from the mAb b78 that mapped to the C-terminal domain blocked anti-GAD65 in sera that contained GAD enzyme inhibitory activity, whether from patients with Stiff Person Syndrome [20], or a subset of patients with ketosis-prone type 1 diabetes [28]. Also, reactivity that mapped to the N-and C-terminal domain inhibitable by rFab from mAb DPD was associated with a higher b-cell functional reserve and a more benign clinical course [28]. Taken together, these epitope mapping studies have suggested that there are differences in the epitopes recognized by different populations of patients.…”
Section: B Cell Responses To Gad65mentioning
confidence: 89%
“…Moreover, progressively increasing levels of b96.11-inhibitable reactivity correlated with high risk HLA-DQ alleles in a longitudinal study on the progression to overt diabetes in anti-GAD65-positive children [29]. By contrast, rFab from the mAb b78 that mapped to the C-terminal domain blocked anti-GAD65 in sera that contained GAD enzyme inhibitory activity, whether from patients with Stiff Person Syndrome [20], or a subset of patients with ketosis-prone type 1 diabetes [28]. Also, reactivity that mapped to the N-and C-terminal domain inhibitable by rFab from mAb DPD was associated with a higher b-cell functional reserve and a more benign clinical course [28].…”
Section: B Cell Responses To Gad65mentioning
confidence: 96%
See 1 more Smart Citation